Challenges with Implementing Oral Exams in Post-Secondary Mathematics Courses - Milica Videnovic (Indonesian Journal of Mathematics Education, 2020)
In this study, seven mathematics professors and instructors were interviewed to share their thoughts about implementing oral assessment in mathematics courses in Canada and the United States, where oral assessment in mathematics is not part of the educational system. Four out of seven mathematics professors and instructors were educated in Poland, Romania, Bosnia, and Ukraine, and they are currently teaching mathematics at a university in Canada. The other three professors were educated in Canada, Germany, and the United States, and they are currently teaching at a university in Germany. Five participants had previously experienced oral examination in mathematics, while the other two had never been exposed to oral examination in mathematics throughout their schooling. The results showed that implementing oral assessment in mathematics courses at the university level in Canada and the United States might raise some students’ and professors’ concerns.